Novel trends in resilience assessment of a distribution system using synchrophasor application: A literature review. (19th June 2021) - Sonal,; Ghosh, Debomita
Summary: The gradual sprawl of power system toward smart grid and enhanced integration of distributed energy resources at the distribution end is transforming the conventional distribution system and is eventually making it self‐sustained. The distribution system is thus continuously evolving to prepare itself for any unforeseen natural, man‐made, and complex events. These events may impact the distribution system as high‐impact low‐frequency (HILF) scenarios. The high intensity and widespread damage of the power system due to HILF scenarios necessitate resilience. Resilience analysis aims to identify these region‐specific vulnerabilities of the electricity network and implement appropriate methods to quickly restore the system to its predisturbance state. Further to enhance the network visibility and situational awareness, integration of synchrophasor to resilience is significant. Therefore, synchrophasor technology integrated with resilience provides online wide area visibility of the distribution system. Using synchrophasor for resilience assessment propels an agile network for coordinating accurate and timely analysis of the system parameters. Therefore, understanding the concept of resilience, its evolution, detailed overview, synchrophasor‐based resilience (SBR) methods as well as its applications are necessary. This article outlines the key points of the synchrophasor technology based resilience technique, its significance, and lays a foundation for continuing research in this area. It offers detailed insight into the comprehensive review of this evolving concept. The article majorly focuses on all the aspects of SBR, its necessity in performance evaluation, synchrophasor measurement based resilience enhancement methods, and application of different SBR techniques in the distribution system. A detailed comparative analysis of SBR features, sample efficiency, result accuracy, merits, and demerits based on available literature is provided. Finally, future perspectives are discussed for implementing resilience assessment using synchrophasor technology in the distribution system. Abstract : Scheme of generic synchrophasor based resilience for distribution system.